Design and characteristics of hydroxyapatites: Effect of radiation - Bhavsar J.; Tufail A.; Gautam P.; Arnold B.; Choa F.-S.; Kelly L.; Cullum B.; Smith P.; Su C.H.; Mandal K.D.; Singh N.B. (My University, 2025)
We have prepared silicate based hard materials and have processed it with organic flux. Because of the bioactivities of hydroxyapatites with tissues, this class of materials have attracted interest for bone applications. We have utilized low temperature processing techniques. Organic melt was used and the directional solidification method to cast the shaped sample. This organic treated material has different characteristics than coarsened oxide materials. Our approach involved low temperature processing using nano and micron sized powders of the material system Na2OK2O- CaO- MgO-Ga2O3-SiO2, and titanates were processed by sintering and grain growth. Our results indicate that substitution of gallium and magnesium or titanium with some variation in processing methods have great potential to improve the glassy characteristics without decreasing the mechanical properties of bones. Effect of radiation on bone was studied by exposing with commercially available Cs137 gamma ray source. It was observed that electrical resistivity increased due to radiation exposure for this system. © 2018 SPIE.